Multi-layer optimization algorithm. (March 2022) - Abdalla, M; Yamin, J; Al-Khawaldeh, E
The optimization of experimental results has repeatedly posed major challenges for scientist and engineers. In this work, a systematic multi-layer optimization scheme is proposed in conjunction with particle swarm optimization algorithm to locate a global optimum that fits a cost function. The technique utilizes SP-lines to form three-dimensional patches surfaces from experimental data in multi-layer fashion and incorporates a multi-layer search using particle swarm optimization. The novel technique is illustrated and verified over two layers of experimental data to show its effectiveness.